APPLICATION OF THE MCKINSEY MODEL IN ORGANIZATIONAL CHANGE AT BANK SYARIAH INDONESIA KCP JEMBER KARIMATA - Anisa Anisa; Nurul Setianingrum (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Organizational change is a vital process in the growth and survival of an organization. The seven key elements that must align and interact harmoniously within an organization are: Strategy, Structure, Systems, Staff, Style/Culture, Shared Values, and Skills. The type of research used in this research is descriptive research using a qualitative approach. The data collection techniques used were observation, interviews and documentation. The data analysis technique is descriptive and the data validity technique uses source triangulation. The results of this research show that 1. the implementation of McKinsey's business strategy has gone very smoothly and has had a significant positive impact on the growth of the banking institution. As a result of implementation, BSI KCP Karimata was able to improve service quality and customer satisfaction. Operational efficiencies obtained through the McKinsey model also contribute positively to profitability and strengthen the financial foundation of BSI KCP Karimata. 2. The profits obtained after implementing the McKinsey model, namely the main profits obtained by BSI KCP Jember Karimata, further strengthen BSI's position as the largest sharia bank in Indonesia and in 2023 BSI will crawl up to the top 10 national banks. The challenge is that there are still some employees who find it difficult to adapt to new regulations or strategies from BSI KCP Jember Karimata.